2004
DOI: 10.4049/jimmunol.172.10.6435
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25bright Regulatory T Cells Actively Regulate Inflammation in the Joints of Patients with the Remitting Form of Juvenile Idiopathic Arthritis

Abstract: This study investigates the role of CD4+CD25+ regulatory T cells during the clinical course of juvenile idiopathic arthritis (JIA). Persistent oligoarticular JIA (pers-OA JIA) is a subtype of JIA with a relatively benign, self-remitting course while extended oligoarticular JIA (ext-OA JIA) is a subtype with a much less favorable prognosis. Our data show that patients with pers-OA JIA display a significantly higher frequency of CD4+CD25bright T cells with concomitant higher levels of mRNA FoxP3 in the periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
289
2
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 365 publications
(324 citation statements)
references
References 40 publications
23
289
2
6
Order By: Relevance
“…A similar subpopulation of CD4 + CD25 high T cells is present in human peripheral blood and lymphoid organs [6][7][8][9][10][11][12][13]. From a few recent studies, it appears that T reg numbers are reduced or their function is impaired in patients with various autoimmune disorders [17][18][19][20][21][22][23][24]. The impact of CD4 + CD25 high T cells in immunoregulation is critically supported by observations of Bennett et al [37] who demonstrated that mutations of Foxp3, a transcription factor which is essential for CD4 + CD25 high T cell function, cause the immune dysregulation, polyendocrinopathy, enteropathy, and X-linked syndrome (IPEX).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar subpopulation of CD4 + CD25 high T cells is present in human peripheral blood and lymphoid organs [6][7][8][9][10][11][12][13]. From a few recent studies, it appears that T reg numbers are reduced or their function is impaired in patients with various autoimmune disorders [17][18][19][20][21][22][23][24]. The impact of CD4 + CD25 high T cells in immunoregulation is critically supported by observations of Bennett et al [37] who demonstrated that mutations of Foxp3, a transcription factor which is essential for CD4 + CD25 high T cell function, cause the immune dysregulation, polyendocrinopathy, enteropathy, and X-linked syndrome (IPEX).…”
Section: Discussionmentioning
confidence: 99%
“…Implication of T reg in human autoimmune disease is currently under intense investigation. Either reduced numbers or suppressive capacities of T reg were recently reported in patients affected by type-1 diabetes [17,18], juvenile idiopathic arthritis [19], systemic lupus erythematosus [20], hepatitis C-associated mixed cryoclobulinemia vasculitis [21], autoimmune polyglandular syndrome type II [22], and psoriasis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Several aspects of immune dysregulation in JIA have been described, including alteration of regulatory T cell numbers, as well as abnormal chemokine and cytokine production, especially IL-1β, IL-6 and TNF-α [2][3][4][5]. Among the cytokines, IL-18 should also be particularly interesting with respect to the pathogenesis of JIA.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter studies, the underlying defect accounting for the inability of the patient's Tregs to suppress lymphocyte proliferation and/or cytokine production could not be identified. Other authors reported that Tregs isolated from patients affected by various types of rheumatoid disorders (rheumatoid arthritis, spondyloarthropathies, and juvenile idiopathic arthritis) presented no apparent functional deficiency (32)(33)(34). Comparison between these studies is complicated by the fact that a means of defining phenotypically Tregs in humans is still lacking.…”
Section: Global Natural Regulatory T Cell Depletion In Active Systemicmentioning
confidence: 99%